Solar based home security / Muhammad Nazmi, Muhammad Azril Zainal and Muhammad Ammar Jusop - Nazmi Mustapa, Muhammad; Zainal, Muhammad Azril; Jusop, Muhammad Ammar (2015)
The “Solar-Based Home Security (SBHS)” is the project which is the system that makes an alarm when intruders enter your home. This idea adapted because there are many robbery cases and this project will be upgraded the functionality to give full specs security at your home and make people feel safe. This system has two main circuit which is solar charger control and the microcontroller of the sensor, led and buzzer. The main of this project is the renewable energy due to concept Final Year Project. In this project the renewable energy that is solar as energy supply. In the solar controller circuit charger, this project has IC LM7805 voltage regulator which act to control the voltage from supply to the Arduino circuit. There are three led that shows the condition of this circuit. In the last is the USB circuit is added to supply the voltage from battery to the Arduino microcontroller. Furthermore for the alarm system the Arduino microcontroller, the main function of the Arduino microcontroller is to control all the input and process the input signal and sent to the output. In this project PIR sensor as the input and the output is buzzer and led light. Lastly, this project is one of the system that related to the security.